The 5th Conference on Information and Knowledge Technology 2013
DOI: 10.1109/ikt.2013.6620029
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid CDN-P2P architecture: Replica content Placement Algorithms

Abstract: Hybrid CDN-P2P architecture is a combination of pure Content Distribution Networks (CDNs) and Peer-to-Peer (P2P) networks. This architecture relies on CDN and P2P complementary advantages. This paper discusses Replica Placement Algorithms (RPAs) in hybrid CDN-P2P architecture. There are two constraints in the used model; one is the server storage capacity constraint and another is an upper bound for the number of replicas for each content. RPA has been considered as a constraint p-median problem. Constraint p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Nevertheless, any replication algorithm is insufficient due to the high transient nature of wireless and mobile devices. Khalaji and Analoui 27 constructed a novel real‐time streaming scheme in which a new hybrid CDN‐P2P strategy established buffers in CDN servers and P2P networks. Due to the dramatic increase in mobile multimedia data, the user experience has plummeted.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, any replication algorithm is insufficient due to the high transient nature of wireless and mobile devices. Khalaji and Analoui 27 constructed a novel real‐time streaming scheme in which a new hybrid CDN‐P2P strategy established buffers in CDN servers and P2P networks. Due to the dramatic increase in mobile multimedia data, the user experience has plummeted.…”
Section: Related Workmentioning
confidence: 99%
“…The study outcome has been found to minimize cost of transport and storage of data. Mathematical approach of Lagrangian relaxation has been adopted by Khalaji and Analoui [22] for the sole purpose of minimizing the complexity issues associated with content placement problems to show the outcome with optimal cost effectiveness. Usage of dynamic programming-based approach for solving similar problem was discussed by Chen and Chen [23] with the study outcome to exhibit low complexity.…”
Section: A Efficient Content Placementmentioning
confidence: 99%